Improvement of Dynamical Stability Using Interline Power Flow Controller - BANAEI, M. R.; KAMI, A.-R. (Advances in Electrical and Computer Engineering, 2010)
This paper presents a novel linearized Phillips-Heffron model of a power system installed with an Interline Power Flow Controller (IPFC) in order to studying power system stability. In addition, a supplementary controller for a novel modeling IPFC to damp low frequency oscillations with considering four alternative damping controllers is proposed. In this paper selection of effectiveness damping control signal for the design of robust IPFC damping controller to variations in system loading and fault in the power system are discussed. The presented control scheme not only performs damping oscillations but also the independent interline power flow control can be achieved. MATLAB simulation results verify the effectiveness of the IPFC and its control strategy to enhance dynamical stability.